2018
DOI: 10.1084/jem.20181345
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells act as gatekeepers for LTβR-dependent thymocyte emigration

Abstract: Thymic emigration is essential for establishing T cell immunity. We show the requirement for LTβR segregates from its control of medullary epithelium. Instead, our study demonstrates LTβR expression by the endothelium acts to rate limit thymocyte egress via perivascular routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…Importantly, in LTβR TEC mice, selective intrathymic targeting of LTβR deletion to TEC with Foxn1 Cre directly demonstrates that loss of iNKT cells in these mice is due to defective intrathymic development. Moreover, unaltered thymus emigration in LTβR TEC mice 49 also argues against an impact on iNKT cells caused by defects in this process. Thus, our data indicate that TEC expression of LTβR influences intrathymic development of NKT cells in the thymus, and that this then causes iNKT cell defects in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in LTβR TEC mice, selective intrathymic targeting of LTβR deletion to TEC with Foxn1 Cre directly demonstrates that loss of iNKT cells in these mice is due to defective intrathymic development. Moreover, unaltered thymus emigration in LTβR TEC mice 49 also argues against an impact on iNKT cells caused by defects in this process. Thus, our data indicate that TEC expression of LTβR influences intrathymic development of NKT cells in the thymus, and that this then causes iNKT cell defects in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the localization of TPEC at the CMJ would make them an attractive candidate to regulate T-cell egress via these mechanisms. Perhaps in line with this, in the LTβR Endo mouse model which have a T-cell progenitor homing defect, there is also clear indication that thymic egress is also LTβR-endothelial dependent ( 49 ). Thus, LTβR Endo mice exhibit an intrathymic accumulation of mature thymocytes at a similar magnitude as seen in the germline LTβR-deficient mouse thymus ( 48 , 51 ).…”
Section: Thymic Endotheliummentioning
confidence: 83%
“…Thymic portal endothelial cells (TPEC) were identified as Ly6C − P-selectin + and were found to be enriched in vessels at the CMJ, with ~60% of CD31 + vessels at the CMJ found to contain TPEC ( 73 ). Importantly, TPEC are selectively reduced in mice lacking LTβR either in all cells, or in models were LTβR is deleted specifically on endothelial cells using a endothelial-specific Cre mouse model (Tie2 Cre ) crossed with LTβR Flox mice, to generate LTβR Endo mice ( 49 , 73 ). Loss of TPEC in these mice is accompanied with a significant reduction in the number of early T-cell progenitors (ETP) within the thymus, indicating a T-cell progenitor homing/colonization defect ( 73 , 74 ).…”
Section: Thymic Endotheliummentioning
confidence: 99%
“…LTβR-dependent, mFb-associated genes such as extracellular matrixes or proteases might play various roles in organizing the cellularity and function of mTECs. LTβR signal also controls the expression of cell adhesion molecules ICAM-1 and VCAM-1 in mFbs, suggesting the role of mFbs in regulating immune cell trafficking in the thymus ( 72 , 94 ).…”
Section: Medullary Fibroblastsmentioning
confidence: 99%
“…It has been shown that pericytes are responsible for the production of the S1P that promotes thymocyte egress ( 116 ). The trans-endothelial entry of ETPs and exit of mature T cells are regulated by the LTβR expressed in endothelial cells and pericytes ( 94 , 117 ). Although the cellular source of LTβR ligands in the context of controlling cell traffic and the significance of this regulatory mechanism are not yet known, the LTβR may be a potential target to efficiently restore T cell production capacity in certain therapeutic situations such as bone marrow transplantation ( 117 ).…”
Section: The Thymic Vasculature and Blood–thymus Barriermentioning
confidence: 99%